Flood-Irrigated Corn Cost-Return Budget - O'Brien, Daniel M.; Dumler, Troy J. (My University, 2000)
This publication projects a budget that reflects expected income and costs based on flood-irrigated corn production.
MF578_2000_10
Keywords: MF578; Economics; Crops; MF